1994
DOI: 10.1111/j.1468-5957.1994.tb00331.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pre‐announcement Share Price Behaviour of Uk Takeover Targets

Abstract: This paper examines the sources of pre‐bid announcement abnormal returns (ARs) accruing to target companies’ shareholders. To control for publicly available information, targets are classified as either identified or unidentified. The paper finds that prior disclosure of bid related information does give rise to pre‐bid ARs. For identified targets there is no evidence that these ARs arise from trading on unpublished price sensitive information. For unidentified targets, trading on unpublished price sensitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…To the contrary, Holland and Hodgkinson (1994) found that past performance has no effect on takeover likelihood in the UK. Similarly, Alcade and Espitia (2003) found no support for the view that acquisitions exist to replace incumbent managers in Spanish companies.…”
Section: Takeover Attractivenessmentioning
confidence: 70%
See 4 more Smart Citations
“…To the contrary, Holland and Hodgkinson (1994) found that past performance has no effect on takeover likelihood in the UK. Similarly, Alcade and Espitia (2003) found no support for the view that acquisitions exist to replace incumbent managers in Spanish companies.…”
Section: Takeover Attractivenessmentioning
confidence: 70%
“…Over the last decade or so only 18 per cent of the takeovers were hostile (Hartzell, et al, 2004), which indicate that most of the takeovers do require support of the incumbent managers to progress. Furthermore, empirical evidence show that acquisitions have largely benefited target companies shareholders (Loughran and Vijh, 1997;Holland and Hodgkinson, 1994) and therefore, by resisting takeover attempts, CEOs can cost acquiring shareholders significant acquisition premiums. Minimizing the cost of the conflict between a CEOs desire to keep their job and shareholders' wealth maximisation is one of the major reason for the existence of golden parachutes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations